PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN DI DISTRIBUTOR OBAT PT X: STUDI KUANTITATIF PADA PEDAGANG BESAR FARMASI - Husnul Muamilah; Siwi Sumirat (IONTech Journal, 2026)
This study aims to examine the effect of workload on employee performance at PT X, a pharmaceutical distributor (Pedagang Besar Farmasi/PBF). This research uses a quantitative approach with a saturated sampling technique, involving all employees of PT X (n=11). Data were collected using a questionnaire as primary data and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Workload was measured using nine indicators, and employee performance was measured using nine indicators. The results show that workload has a positive but not statistically significant effect on employee performance (t=1.955; p=0.051). These findings indicate that, within the observed sample, there is insufficient evidence to confirm a significant effect of workload on performance at the 5% significance level. This study is expected to provide input for PT X in evaluating workload management to support performance improvement and organizational objectives.